Binary Addition and Subtraction - Patrick, Dale R.; Fardo, Stephen W.; Chandra, Vigyan (Vigs); Fardo, Brian W. (Electronic Digital System Fundamentals, 2023)
Digital systems are called on to perform several arithmetic functions in their operations. As a rule, the circuitry of a digital system must deal with binary numbers. The internal circuitry must manipulate the data very quickly and accurately. The subject of digital arithmetic can be very complex when all of the methods of computation and the theory behind it are understood. Special arithmetic ICs are readily available as off-the-shelf items. The addition is a mathematical operation in which two or more numbers are combined together to obtain a simple equivalent quantity. The counting method of addition is rather slow and somewhat awkward to handle when large numbers are involved. The addition of binary numbers is similar in nearly all respects to the addition of decimal numbers. Logic gates are used in digital systems to accomplish the arithmetic operation of binary addition. The logic gate needed for this operation is somewhat unique.